Determination of ionization constants for some aromatic Schiff base acids derived from a benzyl compound with aromatic amines - Adel Azzoz; Mahmoud Saeed; Khalil Al-Nuaimi (College of Education for Pure Sciences, 2006)
ABSTRACT The paper is concerned with the preparation and determination o'f pKa for four acidic Schiff bases from the reaction of benzil with other appropriate aromatic primary amines as o,m,p-aminophenols and 4-amino-2-hydroxybenzoic acid. This produces two categories of acidic Schiff bases having a mono phenolic groups in o.m and p-positions and diacidic Schiff base containing a nieta phenolic and para carboxyl group with respect to amine group respectively. The structures of imines under study are confirmed by using some physical methods as melting points, UV, IR and NMR spectra. The potentiomeric method is applied for the determination of pka values of these acidic compounds. This is founded to be fast, simple and precise with an accuracy in the range of ± 0.001 pka unit. The pka values of mono phenolic Schiff bases are found to depend on the positions of phenolic groups on aromatic ring and in the order of increasing para > ortho > rneta. Moreover, the pka of diacidic Schiff base resulted to the evaluation of pka of phenolic group only, with a failer determination of pka value of the carboxyl group. A fixed 25% ethanol -water mixture is used through pKa determination Finally, a suitable interpretation for the last is given and discussed.